Character education implementation for students in grade IV SDN 5 Sindangkasih regency of Purwakarta West Java - Sofyan Mustoip (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2018)
Students are less polite especially to teachers who should be respected. The sense of courtesy can be seen when the students shaking hands to the teacher he met, and say "excuse me" when passing the more mature person, and the number of learners who use slang compared to use sundanese. Thus, this study has the aim to describe in full the pattern of implementing character education as an effort of Elementary school in carrying out character education activities for students in grade IV in order to shape the character of students through the local wisdom of Sundanese culture. The method used in this study is a qualitative descriptive method that uses an interactive model in data analysis activities including data collection activities, data reduction, data presentation, and conclusion drawing. Data collection was carried out through data triangulation, namely interviews, observation, and documentation. The research subjects consisted of one school principal, three class teachers, one school guard and all fourth grade students. The results showed, the character values pursued by that school’s are religious values, discipline, independence, respect for achievement, communicative, and responsibility. This is in accordance with the vision and mission of SDN 5 Sindangkasih which is to create a school that is capable of producing superior generations who are religious, mastering science and technology, and loving Indonesian culture.